Air pollution XXVII - Passerini, G.; Borrego, C.; Longhurst, James W. S.; Lopes, M.; Barnes, J. (Jo) (WIT transactions on ecology and the environment, 2019)
In its 27th edition the conference on Air Pollution continues to produce valuable research on issues related to the modelling, monitoring and management of air pollution. The papers included in this book continue a wide ranging collection of high quality research works that develop the fundamental science of air pollution.